Periodic entropy coder initialization for wavefront decoding of video bitstream - Misra, Kiran; Zhao, Jie; Segall, Andrew (2011 18th IEEE International Conference on Image Processing, 2011)
In this paper, we outline a coding strategy that initializes the entropy coding engine of a video codec at pre-defined locations within a bit-stream. Coupled with the causal dependencies of state-of-the-art video coding systems, this enables wavefront processing of the entropy decoding and reconstruction process simultaneously. Approaches to wavefront processing have been considered by others, and those methods either address the reconstruction process solely or require transmitting image data in non-raster scan order. Here, our key contribution is that we enable simultaneous entropy/reconstruction wavefront processing while still preserving a raster scan strategy. In this paper, we describe the system, as well as different strategies for initializing the context models. The performance of the proposed methods is evaluated, and the bitrate increase is shown to be nominal.